Cyber Conflict and International Relations: Liberalism, Neorelaism and Consructivism - Bayrak, Sabri (Cyberpolitik Journal, 2021)
Parallel to the arrival in cyberspace, a new dimension has been added to the meaning of the concept of conflict, which is one of the important concepts in International Relations, and the concept of cyber conflict has emerged as a component of physical conflict. With the emergence of the concept of cyber conflict, academics have tried to define this definition. These studies were not only sufficient with the effort to define cyber conflict, but also related to the cyber conflict-emergence process, experiments and results. Although there are many studies on cyber conflict, when the literature is examined, the lack of theory on the common issue ignored by research on cyber conflict stands out. Because the cyber conflict analysis made from the International Relations perspective is almost nonexistent. It would not be an exaggeration to reconcile cyber conflict and international relations theories as a new dimension of conflict, based on the presumption that the knowledge conflict that reveals the International Relations discipline. For this reason, its main purpose is to analyze international relations theories and cyber conflict. It is thought that conducting cyber conflict analysis from a theoretical perspective will make an important contribution to the literature.